2015
DOI: 10.1155/2015/378678
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Intragranular Acicular Ferrite Nucleation Induced by Mg-Al-O Inclusions

Abstract: The features of inclusion and microstructure for carbon structural steel containing Mg-Al-O inclusions were studied through the scanning electron microscope (SEM) and Energy Dispersive Spectrometer (EDS). It can be seen that, in Mg-Al-O inclusions, the elements of Mn, Si, and S coexist, and their central mole ratio of Mg/Al varies in a wide range. This value for most inclusions is larger than 0.5, which suggests the formation of solid solution between MgAl2O4and MgO. After etching, the typical microstructure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…Having cerium sulfide has been effective for the formation of AF. Our results are in agreement with other researchers’ 1 2 3 4 5 6 7 8 9 10 11 12 . Figure 4f is related to sample No.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Having cerium sulfide has been effective for the formation of AF. Our results are in agreement with other researchers’ 1 2 3 4 5 6 7 8 9 10 11 12 . Figure 4f is related to sample No.…”
Section: Resultssupporting
confidence: 94%
“…Many researchers have investigated on improving the behavior of non-metallic inclusions during solidification of steel. It was found that depending on the chemical composition and their size, they can have different impact on properties of steel, starting from strongly negative to almost conditioning obtaining desired mechanical properties 1 2 3 4 .…”
mentioning
confidence: 99%
“…For example, about the origin of MDZ around Tibearing particles, there are still two viewpoints: (1) the MDZ is produced by MnS precipitation on the Ti 2 O 3 inclusion during cooling process [10]; (2) Ti 2 O 3 can absorb Mn atoms from the steel matrix [11]. Our previous studies also indicate that MnS precipitates on Mg-bearing inclusion [7]. Thus, what is the relationship between MnS precipitation and IAFs nucleation?…”
Section: Introductionmentioning
confidence: 96%
“…In 2015, our group has proposed Mn-depletion zone (MDZ) theory to explain the mechanism of IAF nucleation induced by Mg-Al-O inclusions [7]. This is based on the following experimental and theoretical evidences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation